2013
DOI: 10.1002/ppsc.201300294
|View full text |Cite
|
Sign up to set email alerts
|

Blue Luminescent Graphene Quantum Dots by Photochemical Stitching of Small Aromatic Molecules: Fluorescent Nanoprobes in Cellular Imaging

Abstract: Blue fluorescent graphene quantum dots (GQDs) are synthesized from small haloaromatic molecules by laser photochemistry. The process involves a bottom‐up photochemical stitching mechanism of the free radicals generated by irradiation of ultraviolet photons (λ = 248 nm) on o‐dichlorobenzene. The GQDs are further demonstrated to be of importance as fluorescent nanoprobes in bioimaging of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 25 publications
3
50
0
Order By: Relevance
“…Moreover, due to their similarity in structure, polycyclic aromatic hydrocarbons are generally regarded as nanoscaled fragments of graphene, which gives them great promise for preparing monodispersed GQDs with precisely tailored structure, morphology and size. Aromatic molecules, such as diphenylacetylene [39], hexa-peri-hexabenzocoronene [29], pyrene [123,124], benzo[a]pyrene or naphtho [2,pyrene [123], 4-bromo-3-iodobenzoic acid [125][126][127] and o-dichlorobenzene (DCB) [128], are employed as precursors through successive carbonization, oxidization, surface functionalization and reduction process, or utilizing stepwise solution chemistry strategies to prepare GQDs successfully. Furthermore, doping and/or surface passivation are effective methods to modulate the electronic density of bulk semiconductor materials and to tune their optical and electrical properties.…”
Section: Synthesis and Optical Property Of Gqdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, due to their similarity in structure, polycyclic aromatic hydrocarbons are generally regarded as nanoscaled fragments of graphene, which gives them great promise for preparing monodispersed GQDs with precisely tailored structure, morphology and size. Aromatic molecules, such as diphenylacetylene [39], hexa-peri-hexabenzocoronene [29], pyrene [123,124], benzo[a]pyrene or naphtho [2,pyrene [123], 4-bromo-3-iodobenzoic acid [125][126][127] and o-dichlorobenzene (DCB) [128], are employed as precursors through successive carbonization, oxidization, surface functionalization and reduction process, or utilizing stepwise solution chemistry strategies to prepare GQDs successfully. Furthermore, doping and/or surface passivation are effective methods to modulate the electronic density of bulk semiconductor materials and to tune their optical and electrical properties.…”
Section: Synthesis and Optical Property Of Gqdsmentioning
confidence: 99%
“…Also, nitrogen and sulfur co-functionalized GQDs are successfully obtained using nitrogen and sulfur containing compounds of 1-methyl-1-propylpiperidinium bis(trifluoromethylsulfonyl) imide [68], polythiophene [136] and thiourea [110]. Moreover, o-dichlorobenzene [128], ATP [119,120] and 1-methyl-1-propylpiperidinium bis(trifluoromethylsulfonyl)imide [68] are utilized as sources to prepare chloride-, phosphorus-and fluoride-functionalized GQDs, respectively. The dimensions and heights of graphene sheets in the obtained GQDs range from 1.5 to 100 nm and 0.5 to 5 nm, respectively.…”
Section: Synthesis and Optical Property Of Gqdsmentioning
confidence: 99%
See 1 more Smart Citation
“…It deserved to note that the band gap of all these quantum dots are larger than oligomers. The change of band gap can be due to the quantum size effect in these quantum dots like semiconductor quantum dots [1][2][3][4][75][76][77].…”
Section: Optical Properties Of Poqdsmentioning
confidence: 99%
“…Compared with other polymer dots (Pdots) which primarily consist of π-conjugated polymers, fluorescent copolymer dots could be prepared easily, low cost and low cytotoxicity, so it obtain considerable research in various fields [9][10][11][12]. Wu et al reported highly fluorescent semiconducting polymer dots and applied them to biology and medicine [13].…”
Section: Introductionmentioning
confidence: 99%